Scenario Planning as a New Application Area for TOPSIS - Helena Gaspars-Wieloch (Operations Research and Decisions, 2023)
TOPSIS is a well-known approach applied to multi-criteria decision-making under certainty (M-DMC). However, recently, some analogies between this domain and scenario-based one-criterion decision-making under uncertainty (1-DMU) have been revealed in the literature. Thus, the similarities aforementioned give the possibility to adjust TOPSIS to another area. The goal of the paper is to create a new method for problems with non-deterministic parameters on the basis of TOPSIS ideas. In the suggested approach criteria weights (declared within TOPSIS) are replaced by subjective chances of occurrence which are estimated for each scenario. The novel method has an advantage over existing classical decision rules designed for 1-criterion decision-making under uncertainty since within this procedure each payoff connected with a given option is compared with the positive and negative-ideal solutions. (original abstract)